MANAJEMEN RISIKO PENGEMBANGAN INDUSTRI MOCAF (Modified Cassava Flour) DI KABUPATEN JEMBER - Wibowo, Yuli; Herlina, Herlina; Soekarno, Siswoyo; Wiyono, Andi Eko; Prihani, Suwita Tri (Jurnal Teknologi Industri Pertanian, 2023)
Mocaf is one of the leading agrotechnopreneurship products in Jember District. As a business activity, mocaf agrotechnopreneurship development is faced with uncertainties that can lead to unwanted risks. This study aimed to manage risk in the development of mocaf agrotechnopreneurship so that it can become a reference for people in Jember District in developing their business. The methods used for risk management in this study included the Supply Chain Operation Reference (SCOR) approach for risk identification, Failure Mode Effect Analysis (FMEA) for risk assessment, fishbone diagrams for risk evaluation, and the Analytical Hierarchy Process (AHP) and Pugh methods for risk mitigation. This study shows that there are many identified potential risks in developing mocaf agrotechnopreneurship in Jember District, some of which are critical risks. Based on the criticality matrix analysis, three main risks have been obtained in developing mocaf agrotechnopreneurship, including perishable raw materials, low public knowledge about mocaf, and increasing prices of cassava as a raw material. Evaluation regarding the causes of the three risks includes human factors, methods, facilities, and the environment. Risk mitigation results show that the strategy that can be applied is to set particular specifications for raw materials to deal with perishable raw materials, conduct education through various media to increase public knowledge, and establish partnerships with farmers or collectors to overcome rising raw material prices. Keywords: Jember District, leading agrotechnopreneurship, mocaf, potential risks, risk management